Effect of seed breaking dormancy treatments on Prosopis farcta L. seed collected from desert and plantation ecosystems of Semnan - fatemeh shamsodin; alireza moshki; homan ravanbakhsh; maryam mollashahi (علوم و فناوری بذر ایران, 2020)
This study aimed to investigate the effects of different treatments on seed germination and survival of seeds in two regions around Semnan, Sokan (as the understory of pine and black locust plantation) and Soofiabad (as a desert shrub land). The amount of germination of these seeds from two region was estimated by 22 treatments through mechanical (scarification by sand paper) and chemical treatments (sulfuric acid, nitric acid, sodium hydroxide), each treatment in three period of time (10, 20 and 30 minute) and control treatment under greenhouse condition. Furthermore, some parameters such as seed germination speed, height and diameter of seedlings were studied by applying 22 different treatments. The results showed that the highest germination and growth of seedlings were observed under physical scarifying treatment and under Sulfuric acid treatment after 10 minutes. Amount of germination in mechanical treatment (scarification by sand paper) in Sokan seed (71 percent) was more than Sofi abad (57 percent), significantly. Increasing the time of sulfuric acid treatment (from 10 to 30 minute) decreased the germination of seeds (maximum germination in Sokan region in 10 minute treatment was 53.4 and in Sofiabad region was 28.3 percent). The germination rate in Sokan forest ecosystem under scarifying treatment and sulfuric acid (10 minutes) was significantly higher (53.4) than those in desert ecosystem Sufi-Abad (28.7). Moreover, the results of electric conductivity test also showed that the Sufi-Abad had lower quality of seeds. As electric conductivity in Sokan and Sofiabad seed was 3.36 and 6.84, respectively.